A peer‐led teaching initiative for foundation doctors. (24th June 2015) - Ramsden, Sophie; Abidogun, Abiola; Stringer, Emma; Mahgoub, Sara; Kastrissianakis, Artemis; Baker, Paul
Summary Background Peer teaching has been used informally throughout the history of medical education. Formal studies within the medical student and allied health care professional communities have found it to be a popular, and highly effective, method of teaching. Context Newly qualified doctors are currently an underused resource in terms of teaching one another. Innovation A committee, made up of newly qualified doctors and postgraduate education staff, was established. Using only a few resources, this committee organised regular, peer‐led tutorials and used educational needs assessment tools, such as questionnaires, to make improvements to early postgraduate training. Implication A realistic and well‐received intervention to improve the teaching of newly qualified doctors, which is feasible in the modern, busy health care setting. Other institutions may find this method and its resources valuable. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Newly qualified doctors are currently an underused resource in terms of teaching one another </boxed-text>